2011
DOI: 10.1259/bjr/51344661
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic adults with isolated, unilateral right pulmonary vein atresia: multidetector CT findings

Abstract: ABSTRACT. We report two cases of a very rare congenital anomaly, i.e. isolated unilateral pulmonary vein atresia. The patients were asymptomatic and the diagnosis was made using multidetector CT (MDCT), which also showed cyst formation in the right lung. Asymptomatic adult cases or association with cystic lung lesions have never been reported in this condition before. Unilateral pulmonary vein atresia without associated congenital heart disease is a rare condition [1]. Patients with congenital unilateral pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 12 publications
(24 reference statements)
0
26
0
Order By: Relevance
“…In the present case, the patient had remained asymptomatic for a long period of time. Similarly, Kim et al have reported two cases of adult patients (23 and 37 years) who were asymptomatic at the diagnosis (4) . The time for development of symptoms or pulmonary arterial hypertension seems to be dependent on the balance between the systemic vessels which supply and those vessels which drain the affected lung (2,4) , in association with the lymphatic system drainage capacity.…”
Section: 7-12)mentioning
confidence: 78%
See 2 more Smart Citations
“…In the present case, the patient had remained asymptomatic for a long period of time. Similarly, Kim et al have reported two cases of adult patients (23 and 37 years) who were asymptomatic at the diagnosis (4) . The time for development of symptoms or pulmonary arterial hypertension seems to be dependent on the balance between the systemic vessels which supply and those vessels which drain the affected lung (2,4) , in association with the lymphatic system drainage capacity.…”
Section: 7-12)mentioning
confidence: 78%
“…Unilateral pulmonary veins atresia is a rare condition, with less than 40 cases reported in the literature until 2010 (4) . Such a condition is characterized by the absence of pulmonary veins on the affected side and presents high morbimortality (2) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the gravity of symptoms, coil embolization and pneumonectomy are the usual forms of treatment (5,6). There have been few radiologic reports about the findings of systemic collaterals to the pulmonary vessels such as interlobular septal thickening, ground-glass opacity and subpleural nodules (1,2,4,7). We present the case of a 20-year-old male, who had been an asymptomatic pulmonary vein atresia and systemic-to-pulmonary collaterals patient.…”
Section: Introductionmentioning
confidence: 98%
“…Unilateral pulmonary vein atresia is a very rare congenital anomaly usually associated with high morbidity and mortality (1)(2)(3)(4). Most of the patients reported were in infancy or early childhood with recurrent episodes of hemoptysis or pneumonia.…”
Section: Introductionmentioning
confidence: 99%